2021
DOI: 10.1155/2021/9292768
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Breast Cancer Screening Methods among Female Community Pharmacists in Jordan: A Cross-Sectional Study

Abstract: Objectives. Our study is aimed at exploring the knowledge and personal practice of breast cancer screening among female community pharmacists in Jordan. Methods. A cross-sectional survey was carried out using a nonrandom sample selection method for pharmacists in community pharmacies. Results. A total of 551 female pharmacists completed the questionnaire. The mean age of pharmacists was 29.1 ± 7.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(68 reference statements)
4
10
3
Order By: Relevance
“…Similar to the current study findings, a study done by in Jordan found that female participants were highly aware of family history as a risk factor. However, only one-third recognized early puberty as a risk factor [ 12 ]. A recently conducted survey in the KSA found results in contrast to the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the current study findings, a study done by in Jordan found that female participants were highly aware of family history as a risk factor. However, only one-third recognized early puberty as a risk factor [ 12 ]. A recently conducted survey in the KSA found results in contrast to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies reported that women with inadequate knowledge regarding risk factors and susceptibility to breast cancer were less likely to accept breast cancer screening methods. Other factors associated with the low uptake of mammogram screening programs were low income, low education, and lack of information regarding available screening methods [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only variables in Table 7 were the statistically significant variables to predict the knowledge score. The following variables were considered for the first step entry: variable(s) entered on step 1: age (years), gender, marital status, education, country from where your last academic degree was obtained, experience (years), attended an educational program on breast cancer, approximate number of patients with breast cancer interacted with per month, perceived knowledge of breast cancer, average number of working h per week, average number of patients interacted with per day, percentage (%) of female patients visiting the pharmacy, number of pharmacists working in the pharmacy at any one shift [ 34 ]. In addition to the answer the following statements (rarely or often): Respond to patient inquiries related to breast cancer warning signs and symptoms and breast cancer early detection and screening tests, provide patients with advice or counseling on breast cancer screening and early detection, provide patients with breast cancer educational materials or self-assessment quizzes, refer patients to special breast cancer screening programs organized by hospitals or cancer organizations.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the questions related to the knowledge, attitudes, and barriers were selected from the literature [ 32–34 ]. As was outlined in a previous study published in 2021 [ 34 ], the questionnaire was divided in to 4 sections – the first section included the sociodemographic and practice variables of community pharmacists, the second section contained 26 items to test the knowledge of the community pharmacists about breast cancer prevalence, risk factors, signs and symptoms, screening methods, and treatment, the third section used 14 questions to study the attitudes and beliefs of the pharmacists and the final section included 9 questions related to the barriers faced by pharmacists in promoting breast cancer health to patients coming into their pharmacy. The detailed questionnaire can be seen in Figure 1 .…”
Section: Methodsmentioning
confidence: 98%
“…In Jordan, inadequate pain management is still a problem [31,32]. Due to lack of studies among HM, the recent studies were conducted among sloid cancers and revealed that more than 80% of cancer patients experienced poor pain management as resulted from inadequate prescribed opioids and non-opioid adjuvants drugs [31,33]. The reasons which interfere with prescribing opioids for cancer patients in Jordan was related to cultural or legal issues [9].…”
Section: Discussionmentioning
confidence: 99%